Political parties : a sociological study of the emergence of leadership, the psychology of power, and the oligarchic tendencies of organization - Michels, Robert (1959)
Estudio sociológico sobre el liderazgo político, la psicología del poder, y las tendencias oligárquicas en las organizaciones políticas.